A Role for RanBP1 in the Release of CRM1 from the Nuclear Pore Complex in a Terminal Step of Nuclear Export - Kehlenbach, Ralph H. (The Rockefeller University Press, 1999)
We recently developed an assay in which nuclear export of the shuttling transcription factor NFAT (nuclear factor of activated T cells) can be reconstituted in permeabilized cells with the GTPase Ran and the nuclear export receptor CRM1. We have now used this assay to identify another export factor. After preincubation of permeabilized cells with a Ran mutant that cannot hydrolyze GTP (RanQ69L), cytosol supports NFAT export, but CRM1 and Ran alone do not. The RanQ69L preincubation leads to accumulation of CRM1 at the cytoplasmic periphery of the nuclear pore complex (NPC) in association with the p62 complex and Can/Nup214. RanGTP-dependent association of CRM1 with these nucleoporins was reconstituted in vitro. By biochemical fractionation and reconstitution, we showed that RanBP1 restores nuclear export after the RanQ69L preincubation. It also stimulates nuclear export in cells that have not been preincubated with RanQ69L. RanBP1 as well as Ran-binding domains of the cytoplasmic nucleoporin RanBP2 promote the release of CRM1 from the NPC. Taken together, our results indicate that RanGTP is important for the targeting of export complexes to the cytoplasmic side of the NPC and that RanBP1 and probably RanBP2 are involved in the dissociation of nuclear export complexes from the NPC in a terminal step of transport.